Does infrastructure facilitate trade connectivity? Evidence from ASEAN - C. T. Vidya; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2020)
Infrastructural development is crucial for regional trade integration. This study investigates the extent of regional trade interdependence of the Association of Southeast Asian Nations (ASEAN) and its nexus with infrastructure. We selected 13 countries-ASEAN and three other countries (India, the People's Republic of China, and Japan) for the period 1990 to 2018. Using trade network analysis and the panel fixed-effect method, our findings show that: (1) the regional integration in the region is strong and the countries are well interconnected; (2) there is no "center-periphery" structural difference in the region; (3) there are, however, emerging trade-intensive paths among a few countries in the region, which implies the emergence of "exports hubs" and "suppliers of intermediate goods"; (4) the nexus between the infrastructure index and the trade connectivity are strong; (5) shipping and air transport developments have improved the trade connectivity; (6) trade costs (barriers) affect the trade connectivity negatively; and (7) foreign direct investment and trade agreements have helped in improving ASEAN's trade connectivity.
Keywords: F14; F15; R40; 330; regional trade integration; trade connectivity; trade network models; trade-intensive paths